2002
DOI: 10.1051/eas:2002024
|View full text |Cite
|
Sign up to set email alerts
|

Astrometric Microlensing with the GAIA Satellite

Abstract: GAIA is the "super-Hipparcos" survey satellite selected as a Cornerstone 6 mission by the European Space Agency. GAIA can measure microlensing by the brightening of source stars. For the broad G band photometer, the all-sky source-averaged photometric optical depth is ∼ 10 −7 . There are ∼ 1300 photometric microlensing events for which GAIA will measure at least one datapoint on the amplified lightcurve. GAIA can also measure microlensing by the small excursions of the light centroid that occur during events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…When the impact parameter changes by a large fractional amount over the course of a survey, i.e. ∆b il ∼ b il , there can be nonrepeating anomalies in the apparent motion of a star [36][37][38]41]. As objects in the Galactic halo move at speeds of O(10 −3 c), ∆b il ∼ b il requires b il ∼ 10 −3 pc for a survey of a few years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the impact parameter changes by a large fractional amount over the course of a survey, i.e. ∆b il ∼ b il , there can be nonrepeating anomalies in the apparent motion of a star [36][37][38]41]. As objects in the Galactic halo move at speeds of O(10 −3 c), ∆b il ∼ b il requires b il ∼ 10 −3 pc for a survey of a few years.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of using weak lensing to detect objects in time-domain astrometry has a significant history. Previous work has focused on what we call "mono-blips", rare events where the impact parameter of a source and lens changes by O(1) over the course of a mission [36][37][38]. We have revisited this observable, and shown that current and planned astrometric surveys can use it to detect an exceedingly rare population of compact objects, well below existing limits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a number of candidates for astrometric microlensing in our galaxy that can be detected in the near future [80][81][82]. On the other hand, Klioner [83] points out that unpredictable microlensing noise can spoil the determination of positions and proper motions of the objects resulting from future astrometric missions on a submicroarcsecond level.…”
Section: Preliminary Commentsmentioning
confidence: 99%